Characterization of SARS-CoV-2 worldwide transmission based on evolutionary dynamics and specific viral mutations in the spike protein - Jiluo Liu; Xi Chen; Yan Liu; Jiansheng Lin; Jiaying Shen; Hongwei Zhang; Jianhua Yin; Rui Pu; Yibo Ding; Guangwen Cao (BMC, 2021)
Abstract Background The coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) is pandemic. However, the origins and global transmission pattern of SARS-CoV-2 remain largely unknown. We aimed to characterize the origination and transmission of SARS-CoV-2 based on evolutionary dynamics. Methods Using the full-length sequences of SARS-CoV-2 with intact geographic, demographic, and temporal information worldwide from the GISAID database during 26 December 2019 and 30 November 2020, we constructed the transmission tree to depict the evolutionary process by the R package "outbreaker". The affinity of the mutated receptor-binding region of the spike protein to angiotensin-converting enzyme 2 (ACE2) was predicted using mCSM-PPI2 software. Viral infectivity and antigenicity were tested in ACE2-transfected HEK293T cells by pseudovirus transfection and neutralizing antibody test. Results From 26 December 2019 to 8 March 2020, early stage of the COVID-19 pandemic, SARS-CoV-2 strains identified worldwide were mainly composed of three clusters: the Europe-based cluster including two USA-based sub-clusters; the Asia-based cluster including isolates in China, Japan, the USA, Singapore, Australia, Malaysia, and Italy; and the USA-based cluster. The SARS-CoV-2 strains identified in the USA formed four independent clades while those identified in China formed one clade. After 8 March 2020, the clusters of SARS-CoV-2 strains tended to be independent and became "pure" in each of the major countries. Twenty-two of 60 mutations in the receptor-binding domain of the spike protein were predicted to increase the binding affinity of SARS-CoV-2 to ACE2. Of all predicted mutants, the number of E484K was the largest one with 86 585 sequences, followed by S477N with 55 442 sequences worldwide. In more than ten countries, the frequencies of the isolates with E484K and S477N increased significantly. V367F and N354D mutations increased the infectivity of SARS-CoV-2 pseudoviruses (P < 0.001). SARS-CoV-2 with V367F was more sensitive to the S1-targeting neutralizing antibody than the wild-type counterpart (P < 0.001). Conclusions SARS-CoV-2 strains might have originated in several countries simultaneously under certain evolutionary pressure. Travel restrictions might cause location-specific SARS-CoV-2 clustering. The SARS-CoV-2 evolution appears to facilitate its transmission via altering the affinity to ACE2 or immune evasion. Graphic Abstract